M. Amin Abdullah's Contribution to Contemporary Islamic Studies through the Philosophy of Islamic Sciences - Zulfikar, Eko (Islamic Thought Review, 2024)
This article aims to determine M. Amin Abdullah's contribution to contemporary Indonesian Islamic studies through the Philosophy of Islamic Sciences. This is motivated by the fact that Islamic studies in Indonesia have experienced stagnation and rigidity, so it is necessary to provide the right solution through new methods and approaches. This article uses qualitative methods, library research, and descriptive-analytical data analysis techniques. Thus, this article concludes that Amin Abdullah has succeeded in providing a new paradigm for developing contemporary Indonesian Islamic studies. He presents the Philosophy of Islamic Sciences to deconstruct the reconstruction of Islamic studies by linking classical sciences with contemporary sciences. By offering various concepts of thought from intellectual figures, he produces a framework for Islamic studies that is progressive, new, transformative, fresh, not static, and relevant to the times' demands and science's development. He contributes his thoughts on Islamic studies in Indonesia using multidisciplinary, interdisciplinary, and transdisciplinary methods based on the integration-interconnection scientific paradigm. The results of his thinking can foster a broader foundation for Muslim thinking, and contemporary Islamic studies can face the challenges of a more complex era.